Drug use and abuse - Maisto, Stephen A.; Galizio, Mark ;Connors (Stamford, Connecticut : Cengage Learning Asia Pte Ltd, 2015)
Offers an interdisciplinary approach to various drug issues. This title weaves psychological, historical, cultural, social, biological, and medical perspectives - emphasizing the idea that a drug's effects depend not only on its properties, but also on the biological and psychological characteristics of its user.
Drug use and abuse -- Drug use: yesterday and today -- Drugs and the nervous system -- Pharmacology -- Psychopharmacology and new drug development -- Cocaine, amphetamines, and related stimulants -- Nicotine -- Caffeine -- Alcohol -- Opiates -- Marijuana -- Hallucinogens -- Psychotherapeutic medications -- Other prescription and over-the-counter drugs -- Treatment of substance-use disorders -- Prevention of substance abuse
Includes bibliographical references and index.
Keywords: DRUG ADDICTION